A Contrast on Conductor Galloping Amplitude Calculated by Three Mathematical Models with Different DOFs - Bin Liu; KuanJun Zhu; XiaoQin Sun; Bing Huo; XiJun Liu (Shock and Vibration)
It is pivotal to find an effective mathematical model revealing the galloping mechanism. And it is important to compare the difference between the existing mathematical models on the conductor galloping. In this paper, the continuum cable model for transmission lines was proposed using the Hamilton principle. Discrete models of one DOF, two DOFs, and three DOFs were derived from the continuum model by using the Garlekin method. And the three models were compared by analyzing the galloping vertical amplitude and torsional angle with different influence factors. The influence factors include wind velocity, flow density, span length, damping ratio, and initial tension. The three-DOF model is more accurate at calculating the galloping characteristics than the other two models, but the one-DOF and two-DOF models can also present the trend of galloping amplitude change from the point view of qualitative analysis. And the change of the galloping amplitude relative to the main factors was also obtained, which is very essential to the antigalloping design applied in the actual engineering.